Single gold bipyramids on a silanized substrate as robust plasmonic sensors for liquid environments. Issue 34 (15th August 2018) - Rye, Jan-Michael; Bonnet, Christophe; Lerouge, Frédéric; Pellarin, Michel; Lermé, Jean; Parola, Stéphane; Cottancin, Emmanuel
Abstract : Samples of silanized bipyramids are investigated as single scale plasmonic sensors in various liquid environments and during several months. Abstract : Sensitive, robust and stable sensors are required to bring biosensing techniques from the forefront of research to clinical and commercial settings. To this end, we report on the development of new robust plasmonic sensors consisting of gold nano-bipyramids (BPs) grafted to a glass substrate via silanization, associated with a novel setup based on Spatial Modulation Spectroscopy allowing the measurement of the optical response of individual nano-objects in a liquid environment. We thereby show that changes in the refractive index of the medium around individual silanized BPs can be detected by measuring their plasmonic shift with sensitivities comparable to values reported elsewhere and in good agreement with theoretical calculations. The optical response is furthermore shown to be stable and robust allowing for repeated measurements in different media and storage over many months. This work opens up new perspectives in the field of plasmonic bio-sensing as our setup is readily adaptable to dynamic liquid measurements and a wide range of applications such as the detection of clinically important analytes or pollutants in water.